Identification of genes and proteins associated with anagen wool growth. (9th September 2016) - Zhao, J.; Liu, N.; Liu, K.; He, J.; Yu, J.; Bu, R.; Cheng, M.; De, W.; Liu, J.; Li, H.
Summary: Identifying genes of major effect for wool growth would offer strategies for improving the quality and increasing the yield of fine wool. In this study, we employed the Agilent Sheep Gene Expression Microarray and proteomic technology to investigate the gene expression patterns of body side skin (more wool growing) in Aohan fine wool sheep (a Chinese indigenous breed) in comparison with groin skin (no wool growing) at the anagen stage of the wool follicle. A microarray study revealed that 4772 probes were differentially expressed, including 2071 upregulated and 2701 downregulated probes, in the comparisons of body side skin vs. groin skin (S/G). The microarray results were verified by means of quantitative PCR. A total of 1099 probes were assigned to unique genes/transcripts. The number of distinct genes/transcripts (annotated) was 926, of which 352 were upregulated and 574 were downregulated. In S/G, 13 genes were upregulated by more than 10 fold, whereas 60 genes were downregulated by more than 10 fold. Further analysis revealed that the majority of the genes possibly related to the wool growth could be assigned to categories including regulation of cell division, intermediate filament, cytoskeletal part and growth factor activity. Several potential gene families may participate in hair growth regulation, including fibroblast growth factors, transforming growth factor‐ β, WNTs, insulin‐like growth factor, vascular endothelial growth factors and so on. Proteomic analysis also revealed 196 differentially expressed protein points, of which 121 were identified as single protein points.